PENGARUH MASASE PUNGGUNG TERHADAP PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN NORMAL DI BPM WILAYAH KERJA PUSKESMAS TEGALREJO KABUPATEN MAGELANG TAHUN 2012 - Esti Handayani; Pramono Giri Kiswoyo Politeknik Kesehatan Kemenkes Semarang (Jurnal Kebidanan, 2012)
PENGARUH MASASE PUNGGUNG TERHADAP PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN NORMAL DI BPM WILAYAH KERJA PUSKESMAS TEGALREJO KABUPATEN MAGELANG TAHUN 2012 Esti Handayani & Pramono Giri Kiswoyo Politeknik Kesehatan Kemenkes Semarang ABSTRAK A maternal with physiological labor is rarely carried out measures to reduce the pain of labor, especially in the active phase of first stage. If the pain is not managed properly will increase the anxiety or worry so that production of adrenal hormones increased and make blood vessel is vasoconstriction. It causes blood flow mother to fetus decreased. The fetus will be hipoxia while the mother will have prolonged labor (Gadysa, 2007). One of the actions to reduce labor pain that does not cause adverse effects on mother and fetus is a back massage, which can stimulate the endorsfine nerves so that pain can reduced (Danuatmaja, 2004). The purpose is to determine the influence of back massage on pain reduction in the active phase of the first stage of labor in women with normal delivery in BPM Health Centre Tegalrejo area Magelang District 2012. This type of pre-experimental research with pre-post test method and use ordinal scale. Respondests in this study were 35 people with accidental sampling technique. The data was collected using a scale â€œbuorbonaseâ€ and categorized into five pain scale that is divided into: not pain; mild pain; moderate pain; severe pain; and pain is very severe. The data collected was processed using SPSS version 17 with Wilcoxon test. Before the back massage done respondensts have severe pain level there are 18 or 51.4% of respondents, 42.9% or 15 of respondents experienced moderate pain level, and there are only 2 or 5.7% of respondents who experienced pain is very severe. After the back massage done, the pain largely decreased. Respondents who experienced mild pain there are 9 or 25.7% of respondents. While 20 or 57.2% of respondents experiencing moderate pain level, 6 or 17.1% of respondents still experience severe pain, despite back massage done. There is the influence of back massage on pain reduction in the active phase of the first stage of labor in women with normal delivery of significance p value=0.00 and z=-4.456. Midwives should always gave back massage to normal maternal at the active phase of the first stage of labor to reduce pain. Key words: Back massage, labor pain, woman labor